Restoration of Nucleotide Excision Repair in a Helicase-Deficient XPD Mutant from Intragenic Suppression by a Trichothiodystrophy Mutation - George, James W. (American Society for Microbiology, 2001)
The UV-sensitive V-H1 cell line has a T46I substitution mutation in the Walker A box in both alleles of XPD and lacks DNA helicase activity. We characterized three partial revertants that curiously display intermediate UV cytotoxicity (2- to 2.5-fold) but normal levels of UV-induced hprt mutations. In revertant RH1-26, the efficient removal of pyrimidine (6-4) pyrimidone photoproducts from both strands of hprt suggests that global-genomic nucleotide excision repair is normal, but the pattern of cyclobutane pyrimidine dimer removal suggests that transcription-coupled repair (TCR) is impaired. To explain the intermediate UV survival and lack of RNA synthesis recovery in RH1-26 after 10 J of UV/m(2), we propose a defect in repair-transcription coupling, i.e., the inability of the cells to resume or reinitiate transcription after the first TCR event within a transcript. All three revertants carry an R658H suppressor mutation, in one allele of revertants RH1-26 and RH1-53 and in both alleles of revertant RH1-3. Remarkably, the R658H mutation produces the clinical phenotype of trichothiodystrophy (TTD) in several patients who display intermediate UV sensitivity. The XPD(R658H) TTD protein, like XPD(T46I/R658H), is codominant when overexpressed in V-H1 cells and partially complements their UV sensitivity. Thus, the suppressing R658H substitution must restore helicase activity to the inactive XPD(T46I) protein. Based on current knowledge of helicase structure, the intragenic reversion mutation may partially compensate for the T46I mutation by perturbing the XPD structure in a way that counteracts the effect of this mutation. These findings have implications for understanding the differences between xeroderma pigmentosum and TTD and illustrate the value of suppressor genetics for studying helicase structure-function relationships.